Trends in Transcatheter Versus Surgical Aortic Valve Replacement Outcomes in Patients With Low‐Surgical Risk: A Systematic Review and Meta‐Analysis of Randomized Trials - Sina Kazemian; Parisa Fallahtafti; Mohammad Sharifi; Negin Sadat Hosseini Mohammadi; Hamidreza Soleimani; Arman Soltani Moghadam; Elaheh Karimi; Yaser Sattar; Yaser Jenab; Mehdi Mehrani; Alimohammad Hajizeinali; Mina Iskander; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Limited data exist on long‐term outcomes after transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR). This meta‐analysis aims to elucidate outcome trends following TAVR versus SAVR in patients with severe aortic stenosis and low‐surgical risk. Methods and Results A systematic search was conducted in PubMed, Embase, Scopus, and the Cochrane Library databases from inception until May 2024, to identify studies comparing TAVR versus SAVR in patients with low‐surgical risk (Society of Thoracic Surgeons predicted risk of mortality score <4%). The primary outcome was all‐cause mortality. Secondary outcomes included cardiovascular mortality, stroke, disabling stroke, rehospitalization, myocardial infarction, aortic valve reintervention, permanent pacemaker implantation, and new‐onset atrial fibrillation. Binary random‐effects models were used to compare the risk of each outcome across various follow‐up intervals and the risk of bias was assessed using the Cochrane Collaboration's Risk of Bias‐2 tool. The meta‐analysis included 6 randomized trials including 4682 patients. TAVR was associated with a lower risk of all‐cause mortality than SAVR in the 30‐day (hazard ratio [HR: 0.45] [95% CI: 0.26–0.77], I2: 0%) and 30‐day to 1‐year (HR: 0.55 [95% CI: 0.37–0.81], I2: 16%) follow‐ups. However, the risk of all‐cause mortality was similar during >1‐year follow‐ups. TAVR was associated with a significantly lower risk of cardiovascular mortality, disabling stroke, rehospitalization, new‐onset atrial fibrillation, and a higher risk of permanent pacemaker implantation compared with SAVR during the 30‐day follow‐up. Conclusions TAVR was associated with a lower risk of all‐cause mortality within the first year of post‐procedural follow‐up compared with SAVR. However, the risk of all‐cause mortality was similar in >1‐year follow‐ups.